Faktor-Faktor yang Mempengaruhi Preferensi Gen Z dalam Pemilihan Akomodasi Hotel - Suesilowati; Ratih Dwi Astuti; Yola Yolanda Sukmawat (Bulletin of Community Engagement, 2024)
The tourism industry in Indonesia continues to experience significant developments from year to year. This can be seen from the growth of various types of tourism accommodation such as hotels, resorts and others. The preference of Gen Z and previous preferences differ due to their unique characteristics, such as attachment to technology, environmental awareness and tend to pay more attention to experience in traveling. The purpose of this study is to find out what factors influence Gen Z preferences in the selection of hotel accommodation. This research is included in quantitative research with a descriptive research approach. The data sources used are primary data and secondary data. Sampling technique using the accidental sampling method. Data measurement techniques use the likert scale. Obtained results from this study show that the five indicators include price, quality of product, quality of service, brand and tangible produce agreed value. This became an aspect that Gen Z considered in the selection of hotel accommodation.